A Germination and Survival Study of Mugongo (Ricinodendron rautanenii, Schinz) Under Laboratory and Greenhouse Conditions - Chimbelu, Elliot G. (Indian Forester, 1983)
A germination and survival study on Mugongo (Ricinodendron rautanenii, Schinz) was conducted at Spracuse in the USA under laboratory and greenhouse conditions. The objective Of the study was to determine the germination capacity of Mugongo nuts colleeted from the Southern part of Zambia Rnd observe the survival rate of seedlings resulting from them. Seven types of stratification consisting of gibberelic acid, warm and cold treatments and additional four combinations of the treatments were applied on Mugongo seeds. Results revealed that 16.5 per cent germinated prior stratification. An additional 9.5 per cent germinated after stratification with gibberelic acid. About 46 per cent of the seeds that germinated showed abnormal features. Only 22.5 per cent of the Mugongo seedlings survived up to four months of the growing period; and coincidently 80 per cent of the deda seedlings constituted the abnormally germinated Seeds. It was concluded that Mugongo has a low germination capacity and survival rate. The use of gibberellic acid as a pre-germination treatment is beneficial to Mugongo seeds. However, research is needed to determine other effective pre-germination treatments and the cause of abnormal germination.